Use of the ROSE risk score for predicting mortality and cardiovascular events in adult patients at 7 and 30 days of syncope (2016)
Introduction: The use of the ROSE risk score after syncope provides the possibility of identifying patients at risk of death or other important adverse events after 30 days of admission to the emergency department.Objective: To evaluate the performance of ROSE score in terms of mortality prediction and major adverse events at 7 and 30 days in adult patients with syncope admitted to the emergency department.Materials and methods: A prospective cohort study in patients with syncope who were admitted to the emergency room was performed. An operational analysis of the predictive ability for detection of possible complications was done by calculating sensitivity, specificity, positive and negative predictive values and ROC curves.Results: 60 patients were evaluated. An area under the curve for prediction of mortality or major outcome at 7 and 30 days of 0.62 (95%CI: 0.45-0.78) was obtained, with sensitivity of 60%, specificity of 18.18%, PPV of 6.25% and NPV of 83%.Conclusion: ROSE score showed low sensitivity for predicting mortality or serious outcomes at 7 and 30 days. Its high negative predictive value makes it a useful prognostic tool in low risk patients.